2019
DOI: 10.1136/bmjopen-2018-022414
|View full text |Cite
|
Sign up to set email alerts
|

Who pays and how much? A cross-sectional study of out-of-pocket payment for modern contraception in Kenya

Abstract: ObjectivesOut-of-pocket (OOP) payment for modern contraception is an understudied component of healthcare financing in countries like Kenya, where wealth gradients in met need have prompted efforts to expand access to free contraception. This study aims to examine whether, among public sector providers, the poor are more likely to receive free contraception and to compare how OOP payment for injectables and implants—two popular methods—differs by public/private provider type and user’s sociodemographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
0
26
5
Order By: Relevance
“…It is interesting to note that OOP on FP services resulting from this study is significantly associated with health insurance ownership (public-subsidized compared to public non-subsidized and private insurances) and contraception types (LARC compared to short-acting methods). This finding has a similarity and contrast with the prior research about OOP determinants in several countries 18,19,[21][22][23] . In the Indonesian UHC system, socioeconomic characteristics were determined by health insurance ownerships, wherein public-subsidized refers to lower-income groups, and non-subsidized and private insurance refer to wealthier segments.…”
Section: Table2 Structural Model and Odds Ratio Of Factors Related To Out-of-pocket Expenditures For Contraception Services In Sleman Regcontrasting
confidence: 76%
See 1 more Smart Citation
“…It is interesting to note that OOP on FP services resulting from this study is significantly associated with health insurance ownership (public-subsidized compared to public non-subsidized and private insurances) and contraception types (LARC compared to short-acting methods). This finding has a similarity and contrast with the prior research about OOP determinants in several countries 18,19,[21][22][23] . In the Indonesian UHC system, socioeconomic characteristics were determined by health insurance ownerships, wherein public-subsidized refers to lower-income groups, and non-subsidized and private insurance refer to wealthier segments.…”
Section: Table2 Structural Model and Odds Ratio Of Factors Related To Out-of-pocket Expenditures For Contraception Services In Sleman Regcontrasting
confidence: 76%
“…There was a lack of comprehensive data to estimate OOP expenditure on reproductive health, including FP services. While FP services were intended to be free within the public health system, a study by 18 indicated that only one-half of modern method users reported obtaining their free methods. A study in Burkina Faso also mentioned that reproductive health, including FPthrough the public health center, is paid 19 .…”
Section: Table2 Structural Model and Odds Ratio Of Factors Related To Out-of-pocket Expenditures For Contraception Services In Sleman Regmentioning
confidence: 99%
“…Finally, poverty was reported to be a barrier to access to contraceptives for adolescents. This is a commonly reported determinant of access to health services, particularly in contexts where out-of-pocket payment is prevalent [44,45]. Although contraceptives are provided free of charge in public health facilities in Nigeria, our study has highlighted several supply-side factors that discourage adolescents from seeking health services from public health facilities.…”
Section: Discussionmentioning
confidence: 84%
“…For example, injectables, a short-term method, are the most popular contraceptive in SSA (Department of Economic and Social Affairs at United Nations 2019). In Kenya, all public sector users were supposed to receive contraceptives for free, but users of injectables were more likely to pay compared to users of implants, IUDs, pills, or condoms, indicating women's strong preference for injectables (Radovich et al 2019). If free access to LARC and SARC reflected more resources to cover LARC and some previously not-covered SARC methods, such as injectables, LARC users might switch to injectables when LARC were provided free of charge as defined by the treatment variable.…”
Section: Discussionmentioning
confidence: 99%